Research on bacteria isolated from ocular infections, their antibiotic susceptibility patterns and impact on selection of appropriate therapy - De Araújo, Jorann Attracta; Kukla, Rudolf; Vajrychová, Marie; Ryšková, Lenka; Boštík, Pavel (The new microbiologica, 2024)
Bacterial ocular infections represent a common public health problem affecting people of all age groups. These infections can lead to damage of ocular structures or even a loss of vision. The spectrum of isolated bacteria and their susceptibilities to antibiotics, however, shows geographical variabilities, which can affect the success of most empirically-administered antimicrobial therapies. The aim of this study was thus to analyse bacterial aetiology in culture-positive acute and chronic ocular infections and its antimicrobial susceptibility profile in a large cohort of patients in the Czech Republic. The study also focused on corynebacteria identification, particularly on the prevalence of Corynebacterium macginleyi. A total of 2500 bacterial isolates obtained from 2015 to 2020 in University Hospital Hradec Kralove were included in the study. A total of 2320 (92.8%) bacterial isolates were Gram-positive and 180 (7.2%) were Gram-negative. Staphylococcus aureus was the predominant pathogen, isolated from 15.3% of ocular infections, followed by Enterobacterales, Streptococcus pneumoniae and Haemophilus influenzae, isolated in 2.9%, 1.6% and 1.0%, respectively. Corynebacterium macginleyi was confirmed as the most prevalent species of corynebacteria. Most bacteria showed good susceptibility to fluoroquinolones, chloramphenicol, and aminoglycosides. Gram-positive bacteria were also susceptible to tetracycline. To conclude, this study presents a 5-year assessment of bacterial aetiology of ocular infections in the East Bohemian region. The survey showed clear differences in the susceptibilities of several bacteria to select antibiotics compared to studies from other geographical regions in Europe. This clearly shows that local surveillance of the aetiology and antimicrobial susceptibility of bacteria is essential for adequate empirical therapy of ocular infections.
Keywords: dítě; resistance; Česká republika; Microbial Sensitivity Tests; Aged; Adolescent; Eye Infections, Bacterial; Drug Resistance, Bacterial; Aged, 80 and over; lidé středního věku; oční infekce bakteriální; senioři; antibiotics; předškolní dítě; Bacteria; lidé; Adult; Czech Republic; Middle Aged; dospělí; bacteria; susceptibility profile; kojenec; Female; corynebacterial; bakteriální léková rezistence; senioři nad 80 let; Anti-Bacterial Agents; Male; ženské pohlaví; mikrobiální testy citlivosti; Acute and chronic ocular infections; mladý dospělý; Humans; Child; mužské pohlaví; Young Adult; antibakteriální látky; Infant; Child, Preschool; mladiství